The Effect of Ginger Decoction on Emesis Gravidarum among Trimester I Pregnant Women - Nur Azizah; Rini Kundaryanti; Shinta Novelia (KHD-Production, 2022)
Based on data in Indonesia, the comparison of the incidence of nausea and vomiting leading to pathological or hyperemesis gravidarum is 4: 1000 pregnancies. It is estimated that 50% to 80% of pregnant women experience nausea and vomiting and approximately 5% of pregnant women require treatment for fluid replacement and correction of electrolyte imbalances. The occurrence of pregnancy causes hormonal changes in women because there is an increase in the hormones estrogen, progesterone, and the release of the placental chorionic gonadothropine (HCG) hormone. This study aimed to determine the effect of ginger decoction on the frequency of emesis gravidarum in the first trimester. The design used was a quasi-experimental design. The location of this study was carried out at PMB R. Agustina on July 29, 2021 to August 8, 2021. In this study, the number of samples taken by pregnant women who were experiencing emesis gravidarum were 15 experimental groups and 15 total control groups 30. Independent variable was the ginger decoction, and dependent Variable was emesis gravidarum in first trimester among pregnant women. Research instruments can be in the form of a questionnaire (a list of questions), an observation form. Using the Mann Whitney Test. The results showed that the emesis gravidarum before being given ginger boiled water was 9.07 after being given ginger boiled water was 5.27, it was known that the emesis gravidarum before the control was 8.20 after the control was 6.47. There was an Effect of Giving Ginger decoction on Emesis Gravidarum in Pregnant Women TM 1 (p-value 0.001). It is hoped that it can increase public knowledge and is expected to be useful for respondents in knowing about the effect of ginger drink on reducing the frequency of emesis gravidarium in first trimester pregnant women.